Technical Note: Materials: the development dimensions. (4th August 2014) - Rohatgi, Pradeep
In most developing countries materials technology has a long history; agricultural materials, stone, bronze, iron, clays and ceramics have been used to good effect. However, few countries of the Third World have benefited significantly from the industrial revolution of the past 300 years. Many of the applications of materials science as developed for the needs of First World economies are not directly transferable to use in the Third World. To counter this, research should be directed at developing materials technologies which are smaller, lighter, longer lasting, low cost, low energy and recyclable, based on abundant and renewable resources which can be processed locally using labour–intensive rather than capital–intensive methods.